Managing heritage in Africa - Ndoro, Webber, author.
1 online resource
Keywords: "Managing Heritage in Africa provides a wide-ranging, up-to-date synthesis of heritage management practice in Africa, covering a broad spectrum of heritage issues such as archaeology, living traditions, sacred sites, heritage of pain (slavery), international conventions cultural landscapes, heritage in conflict areas and heritage versus development. Dealing with both intangible and tangible heritage, Managing Heritage in Africa gives an informative insight into some of the major issues and approaches to contemporary heritage management in Africa and situates the challenges facing heritage practitioners. "--Provided by publisher.